COMBINATION OF COCRYSTAL AND BALL MILLING TECHNIQUES TO IMPROVE ETORICOXIB DISSOLUTION - Susanto, Sharon
Etoricoxib (ETR) is one of the selective COX-2 anti-inflammatory agents classified in BCS class II. In this study, an approach was made to enhance the dissolution of etoricoxib through a combination of cocrystal formation and ball milling. Experiments were conducted in situ through direct cocrystal formation using the liquid-assisted grinding method and ex situ through the prior formation of etoricoxib-oxalic acid (ETR-OXA) cocrystals using the solvent evaporation method followed by ball milling. Optimization was carried out by varying the milling time and the type of stabilizer. The types of stabilizers used included Tween 80 (ETROXA-T-BM), Poloxamer 188 (ETR-OXA-P-BM), and a combination of Tween 80- sodium lauryl sulfate (SLS) (ETR-OXA-T-S-BM). In situ experiments yielded low yields (<10%). The cocrystals produced ex situ were then evaluated using Differential Scanning Calorimetry (DSC), Powder X-Ray Diffractometry (PXRD), and Scanning Electron Microscope (SEM). DSC analysis of ETR exhibited an endothermic peak at 130°C, while for ETR-OXA, ETR-OXA-T-BM, ETR-OXA-PBM, and ETR-OXA-T-S-BM, endothermic peaks were observed in the range of 179 - 180°C. Meanwhile, PXRD data for ETR-OXA, ETR-OXA-T-BM, ETR-OXA-PBM, ETR-OXA-T-S-BM showed the same peaks; and they were different from ETR. SEM analysis results indicated that ETR-OXA-T-BM with a milling time of 60 minutes produced nanoparticles that were not individualized. On the other hand, the use of Poloxamer 188 and the combination of Tween 80-SLS resulted in particle sizes > 1 µm. ETR-OXA-T-BM 60 produced the smallest particle size with a d90 value of 5.587 µm and a d10 value of 590 nm, followed by ETR-OXA-P-BM 60 and ETR-OXA-T-S-BM 60 with d90 values of 25.97 µm and 126 µm, and d10 values of 772 nm and 1,599 µm, respectively. The solubility of ETR-OXA, ETR-OXA-T-BM 60, ETR-OXA-P-BM 60, and ETR-OXA-T-S-BM 60 increased significantly after 48 hours in distilled water, with values 20-50 times higher compared to pure ETR. In pH 1.2 buffer media, the solubility of ETR, ETR-OXA, ETR-OXA-T-BM 60, ETROXA-P-BM 60, and ETR-OXA-T-S-BM 60 were 6.77±0.12 mg/mL, 14.60±0.10 mg/mL, 27.36±0.24 mg/mL, 23.57±0.31 mg/mL, and 18.73±0.15 mg/mL, respectively. The solubility increase in pH 4.5 media for ETR-OXA, ETR-OXA-TBM 60, ETR-OXA-P-BM 60, ETR-OXA-T-S-BM 60 ranged between 1-1.3 times compared to pure ETR. Etoricoxib had the lowest solubility in pH 6.8 media, with values of 0.13±0.00 mg/mL, 0.15±0.00 mg/mL, 0.31±0.00 mg/mL, 0.22±0.00 mg/mL, and 0.21±0.00 mg/mL for ETR, ETR-OXA, ETR-OXA-T-BM 60, ETR-OXA- iv P-BM 60, and ETR-OXA-T-S-BM 60, respectively. The dissolution results of etoricoxib from ETR-OXA-T-BM at t30 minutes were 48.96±4.87%, while etoricoxib powder was 28.68±1.35%. This indicates an increase and a difference in the dissolution profile in pH 6.8 phosphate buffer media. ETR-OXA-P-BM 60 and ETROXA-T-S-BM 60 did not show a significant difference in dissolution profile compared to ETR powder, with t30 minute values of 24.68±3.09% and 21.11±6.08%, respectively. Optimization of ball milling time showed that an increase in milling time up to 60 minutes could increase the dissolved amount of etoricoxib. ETR-OXA-T-BM 30 and ETR-OXA-T-BM 45 had t30 minute values of 21.30±6.70% and 22.89±1.45%, respectively. The ETR-OXA-T-BM 60 tablet formulation also showed an approximately 1.6-fold increase in dissolution compared to the ETR tablet in pH 6.8 buffer media. Meanwhile, in pH 1.2 buffer media, both the ETR tablet and ETR-OXA-T-BM 60 tablet had already dissolved more than 85% at the 15-minute mark. The dissolution profiles of the ETR tablet and ETR-OXA-T-BM 60 tablet in pH 4.5 buffer media did not show a significant difference, as indicated by similarity values greater than 50. This study demonstrates that the combination of cocrystal formation and ex situ Ball Milling is a potentially effective approach to enhance the dissolution rate of etoricoxib.